Barreras linguísticas y comprensión de problemas matemáticos en estudiantes del séptimo ciclo de secundaria de la IE N° 60080 Carlos Patricio Olórtegui Saenz 2023 - Murrieta Rios, Jesus Armando (2025)
The objective of the study was to analyze the relationship between the level of linguistic barriers and the understanding of mathematical problems in students of the seventh cycle of secondary school at the I.E. N° 60080 Carlos Patricio Olórtegui Sáenz in the year 2023. A relational research was used with a field, bivariate and transversal design. The sample was made up of 310 students, to whom two questionnaires were applied using the survey technique. The results revealed a p value of .000, lower than the significance level of .05, which allowed us to reject the null hypothesis. Furthermore, the evaluation coefficient (rho = -.522) indicated a moderate negative relationship between language barriers and understanding of mathematical problems. In conclusion, it was found that the reduction of language barriers is associated with an improvement in the ability to understand mathematical problems in high school students.